Pengaruh Keadilan Distributif Kompensasi dan Keadilan Prosedural Kompensasi Terhadap Kecenderungan Kecurangan Akuntansi pada SKPD Kabupaten Ngada - Hermanus Reo; Sabulon Sayang; Lavianus Loy Tunga (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
This study aims to determine the effect of distributive justice compensation and procedural justice of compensation against the tendency of accounting fraud at SKPD Ngada district. The method used in this research is descriptive quantitative. The results of this stdy (1) justice distributive effect on accounting fraud at SKPD Ngada Regency. This is evidenced by the value of the regression coefficient justice distributive with value 0,192 with tcount > ttable (3,251 > 2,010) and a significant level of 0,002 < 0,05. (2) Justice procedural effect on accounting fraud. This is evidenced by the valueof the regression coefficient of procedural justice by 0,407 with tcount > ttable (4,876 > 2,010) and the level of significant 0,000 < 0,05. The great influence of the variables of distributive justice and procedural justice against the tendency of accounting fraud amounted to 4,6%. While the rest the rest 53,4% is explained by other variables outside the model.